ANALISIS PENGELOLAAN DANA DESA DI DESA BALUNG KULON - Ningtias, Putri Marta; Kusuma, Dedi Wijaya; Ningsih, Wiwik Fitria (RISTANSI: Riset Akuntansi, 2024)
This study aims as follows: (1) Evaluation of accountability and transparency in the management of village funds for the development of Balung Kulon Village, Jember Regency. (2) To accelerate village development, reduce the difference between urban and rural areas, and encourage the community to actively participate in making development decisions in Balung Kulon Village, Jember Regency. The author uses qualitative methods and uses qualitative descriptive data analysis in this study. The author collects data by interviews, literature study, and documentation with snowball sampling technique. The results of the study show that Balung Kulon village funds are managed in accordance with Permendagri No. 20 of 2018. This research is an important part of research on village funds and can help increase transparency and accountability in the management of village fun/ds. By analyzing the policies, procedures and management practices of village funds, this research can find problems or problems that may exist in the system and provide suggestions for improving transparency, accountability and better governance.